Enhancement of Tobacco (Nicotiana tabacum L.) Seed Lipid Content for Biodiesel Production by CRISPR-Cas9-Mediated Knockout of NtAn1 - Tian, Yinshuai; Liu, Xinanbei; Fan, Caixin; Li, Tingting; Qin, Huan; Li, Xiao; Chen, Kai; Zheng, Yunpu; Chen, Fang; Xu, Ying (Frontiers in Plant Science, 2021)
Tobacco (Nicotiana tabacum L.) seed lipid is a promising non-edible feedstock for biodiesel production. In order to meet the increasing demand, achieving high seed lipid content is one of the major goals in tobacco seed production. The TT8 gene and its homologs negatively regulate seed lipid accumulation in Arabidopsis and Brassica species. We speculated that manipulating the homolog genes of TT8 in tobacco could enhance the accumulation of seed lipid. In this present study, we found that the TT8 homolog genes in tobacco, NtAn1a and NtAn1b, were highly expressed in developing seed. Targeted mutagenesis of NtAn1 genes was created by the CRISPR-Cas9-based gene editing technology. Due to the defect of proanthocyanidin (PA) biosynthesis, mutant seeds showed the phenotype of a yellow seed coat. Seed lipid accumulation was enhanced by about 18 and 15% in two targeted mutant lines. Protein content was also significantly increased in mutant seeds. In addition, the seed yield-related traits were not affected by the targeted mutagenesis of NtAn1 genes. Thus, the overall lipid productivity of the NtAn1 knockout mutants was dramatically enhanced. The results in this present paper indicated that tobacco NtAn1 genes regulate both PAs and lipid accumulation in the process of seed development and that targeted mutagenesis of NtAn1 genes could generate a yellow-seeded tobacco variety with high lipid and protein content. Furthermore, the present results revealed that the CRISPR-Cas9 system could be employed in tobacco seed de novo domestication for biodiesel feedstock production.